Evaluation of the oxidative and inflammatory profile of patients with migraine - Vaz, Aline Vasconcellos Martins; Cardoso, Silvia Almeida; Oliveira, Leandro Licursi de; Freitas, Rodrigo de Barros; Almeida, Palloma Porto; Ribeiro, Paula Dutra; Bastos, Daniel Silva Sena; Magalhães, Lucas Vilas Bôas (Ciência e Natura, 2022)
Among one of the most commonly seen and primary headaches is migraine. Oxidative stress and inflammation is discussed to be implicated in the pathogenesis of migraine. However, further knowledge about this issue is necessary because data are in part controversial and the possible underlying mechanisms remain inconclusive to date. To evaluate and compare the oxidative and inflammatory profile of patients with migraine 47 volunteers were divided into 3 groups: 15 women with chronic migraine (WCM); 17 women with episodic migraine (WEM) and 15 men with migraine (MM) and enrolled in this study.Total antioxidant status; the enzymatic activity of the antioxidant agents Catalase (CAT), Glutathione S-transferase (GST) and Superoxide Dismutase (SOD); oxidative stress markers malondialdehyde (MDA) and carbonylated proteins; blood count and neutrophil/lymphocyte ratio; uric acid, c-reactive protein and cholesterol total and fractions were determined in pacients with migraine in the interictal phase. The group male participants (MM) displayed a reduction in total antioxidant status, as well as a lower value for antioxidant enzymes, but had no significant alterations in markers related to damage by oxidative stress compared to women. These findings suggest that there is a difference in the oxidative profile between the sexes among migraine patients. This may allow a better understanding of patients profile with different migraine phenotypes and identify new markers that might help understanding the pathophysiology and migraine patient management.